1998
DOI: 10.1002/chin.199838267
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Aryl Esters and a Coumarin from Argyreia speciosa.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…It also displayed a positive response in the Lieberman–Burchard test. These results suggested that compound 1 possessed a basic triterpenoid skeleton [ 15 ]. The molecular formula of 1 was established as C 33 H 56 O 3 by the pseudomolecular [M+Na] + ion peak at m/z 523.4122 in HR-ESI-MS analysis and was further supported by its 13 C-NMR spectrum which showed signals for all 33 carbons of the molecule, including one set of terminal methylenes (δ C 111.9, 147.4), three oxygenated carbons (δ C 62.8, 71.0, 83.2), and seven methyl carbons (δ C 15.1, 18.1, 19.0, 19.3, 20.7, 21.3, 25.7).…”
Section: Resultsmentioning
confidence: 99%
“…It also displayed a positive response in the Lieberman–Burchard test. These results suggested that compound 1 possessed a basic triterpenoid skeleton [ 15 ]. The molecular formula of 1 was established as C 33 H 56 O 3 by the pseudomolecular [M+Na] + ion peak at m/z 523.4122 in HR-ESI-MS analysis and was further supported by its 13 C-NMR spectrum which showed signals for all 33 carbons of the molecule, including one set of terminal methylenes (δ C 111.9, 147.4), three oxygenated carbons (δ C 62.8, 71.0, 83.2), and seven methyl carbons (δ C 15.1, 18.1, 19.0, 19.3, 20.7, 21.3, 25.7).…”
Section: Resultsmentioning
confidence: 99%
“…The plant has been screened for antiinflammatory (Gokhale et al, 2002), immunomodulatory (Gokhale et al, 2003), and hepatoprotective (Habbu et al, 2008), antimicrobial and antitubercular (Habbu et al, 2009) and nootropic (Habbu et al, 2009) activities. Phytochemical investigations on the roots of A. speciosa have resulted in the isolation of a range of biologically active substances like Flavonoid sulphates (Petra et al, 1999), Stigmasteryl p-hydroxycinnamate and a Coumarin (Srivastava and Shukla, 1998) and many phenolic compounds. We reported the isolation, characterization, antimicrobial antituberculosis efficacy of flavanoid suphates and other fractions of A. speciosa (Habbu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It also displayed positive responses against the Lieberman-Burchard test. These results suggested compound 1 to be a triterpenoid [50]. The molecular formula of 1 was established as C 32 H 52 O 5 by the pseudomolecular [M+H] + ion peak at m/z 517.3896 in HR-FAB-MS analysis and was further supported by its 13 C-NMR spectrum which showed signals for all the 32 carbons of the molecule including one set of acetyl group ( δ C 171.0, 21.3), one carboxylic acid group ( δ C 176.8), one oxygenated quaternary carbon ( δ C 90.1), and one acetoxygenated carbon ( δ C 80.9), respectively.…”
Section: Resultsmentioning
confidence: 99%